Constraints and Strategies for Sustainable Apiculture Perception of Beekeepers in Bihar - Kumar, Ashok; Kumari, Maya; Paswan, Arun Kumar; Prakash, Satya (Indian Journal of Extension Education, 2013)
Based on systematic study, the efforts have been made to identify the major constraints in adoption of standardized bee keeping technologies for enhancing honey production .Also some strategies were suggested for participative approach of  sustainable apiculture based on the experiences of bee-keepers of this region. The study revealed that the prime  constraints perceived by beekeepers were related to technological and economic aspects. The important strategies  suggested by beekeepers included the aspects of trainings, migration beekeeping practices.
Keywords: Bee-keeping; adoption; constraints; strategies